Foetal death due to extensive extra-abdominal umbilical vein Varix with umbilical vein thrombosis: a case report - Qing-Yun Song; Ying Tang (BMC Pregnancy and Childbirth, 2023)
Abstract Background Foetal anaemia and umbilical vein thrombosis are rare pregnancy complications that can increase the risk of perinatal adverse events, which, in severe cases, can lead to foetal death. During pregnancy, umbilical vein varix (UVV) commonly occurs in the intra-abdominal part of the umbilical vein and is associated with an increased risk of foetal anaemia and umbilical vein thrombosis. However, UVV occurring in the extra-abdominal part of the umbilical vein is rare, especially when accompanied by thrombosis. In this case report, we describe a rare case of an extensive extra-abdominal umbilical vein varix (EAUVV), which ultimately resulted in foetal death due to umbilical vein thrombosis. Case presentation In this report, we describe a rare case of an extensive EAUVV that was discovered at 25 weeks and 3 days of gestation. During the examination, there were no abnormalities in foetal haemodynamics. The estimated weight of the foetus was only 709 g. In addition to refusing to be hospitalized, the patient refused close monitoring of the foetus. As a result, we were limited to choosing an expectant therapy. The foetus died 2 weeks after diagnosis and was confirmed to have EAUVV with thrombosis after the induction of labour. Conclusion In the case of EAUVV, lesions are extremely rare, and it is very easy for thrombosis to form, which may result in the death of the child. When determining the next step in the treatment of the condition, the degree of UVV, possible complications, gestational age, foetal haemodynamics, and other relevant factors are strongly connected to the clinical therapy decision, and these factors should be considered comprehensively when making a clinical decision. We recommend close monitoring with hospital admission (to facilities capable of handling extremely preterm foetuses) after variability in delivery for worsening haemodynamic status.